Late events after anti-CD19 CAR T-cell therapy for relapsed/refractory B-cell non-Hodgkin lymphoma - Cordeiro, Ana Costa; Durisek, George; Batista, Marjorie Vieira; Schmidt, Jayr; de Lima, Marcos; Bezerra, Evandro (Frontiers in Oncology, 2024)
The short-term complications from CART are well characterized, but the long-term complications still need to be further investigated. Therefore, herein, we will review the current available literature published on the late adverse events following CART cell therapy.We reviewed published data available from pivotal trials and real-world experiences with anti-CD19 CART (CART19) for adults with lymphoma. We defined late events as occurring or persisting beyond 1-month from CART infusion. We focused our literature review on the following late events outcomes post-CART19: cytopenia, immune reconstitution, infections, and subsequent malignancies.Results: Grade 3-4 cytopenia beyond 30 days occur in 30-40% of patients and beyond 90 days in 3-22% of patients, and usually managed with growth-factor and transfusion support, along with neutropenic prophylaxis. B-cell aplasia and hypogammaglobulinemia are expected on-target off-tumor effect from CART19, and 44-53% of patients have IgG < 400 mg/dL, and around 27-38% of patients receive IVIG replacement.Infection beyond initial month from CART19 are not frequent and rarely severe, but they are more prevalent and severe when patients received subsequent therapies post-CART19 for their underlying disease. Late neurotoxicity and neurocognitive impairment is uncommon and other causes should be considered. TCL after CART is an extremely rare event and not necessarily related to CAR transgene. Myeloid neoplasm is not rare post-CART, but unclear causality given heavily pre-treated patient population already on risk for therapy related myeloid neoplasm.CART19 is associated with clinically significant long-term effects as prolonged cytopenia's, hypogammaglobulinemia and infections that warrants clinical surveillance, but they are mostly manageable with low risk of non-relapse mortality. The risk of subsequent malignancies post-CART19 seems low and unclear the relationship with CART19 and/or prior therapies, but regardless of the possible causality, this should not impact the current benefit risk ratio of CART19 for relapsed/refractory B-cell NHL.